Cultivating intellectual abilities and talents: The 'forgotten' Catholic contribution. (January 2023) - Gellel, Adrian-Mario; Camilleri, Rosienne
The notion of the human person, together with the importance that the Catholic community has, since its inception, given to the educational enterprise, has led various authors, including Augustine, Abelard, and Aquinas, among others, to reflect on the meaning of intellect and talents and their effects on education. Yet such reflections were never standalone considerations but rather built in dialogue, and at times in confrontation, with the classics and secular treatises of the time. After outlining how the Catholic community conceptualizes the human person, this paper will touch upon the concepts of talent as developed and dealt with during the 12th century. The latter period has been chosen on the basis of the developments in pedagogical thought and practices. The paper aims to critically analyse the notion of 'ingenium' (understood as talents, innate abilities) against the main philosophical and pedagogical thought that has animated Catholic educational practices.